Apply the distributive property first:

6x - (3 + 8x) = -11

x = ?

Thank you for the opportunity to help you with your question!

we have :

so :

6x - 3 - 8x = -11

we have 6x- 8x = -2x

- 3 - 2x = -11

- 2x = -11 + 3

-2x = -8

2x = 8

x = 8/2

x = 4

If you don't understand something just ask

Each time you have any other homework just invite me i will give youthe best answer

Good luck

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up